La teología política del katechon: análisis sobre su dimensión farmacológico-escatológica = Abweichender Titel: The Political Theology of Katechon : an analysis of its Pharmacological-Eschatological Dimension - Borja Gallego Pérez de Sevilla, Francisco de (Cauriensia, 2025)
The study of the theological-political figure of the katechon has given rise to numerous interpretations and speculations. This paper seeks to offer an approach to its distinctive pharmacological meaning, which sets it apart from other formulas tied to political sovereignty, both in the ancient world and in modernity. The katechontic mechanism, as a restraining force against evil, simultaneously requires the acknowledgment of evil’s inevitability as the definitive sign of the end times that precedes the Parousia. Deciphering this eschatological dimension of the katechon also demands a comprehension of political theology as an ontological foundation within the human order, in contrast to the Promethean mindset of secular ideologies. The study concludes that the current crisis of the katechon, linked to the dissolution of the state of exception and the rise of consensual violence, reveals an apocalyptic horizon in which order no longer opposes chaos, but rather neutralizes it through the banalization of all conflict. Within this framework, the need arises to revive a substantive political theology capable of reintroducing the eschatological meaning and the spiritual struggle into human history.